Efficacy and safety of vunakizumab in moderate-to-severe plaque psoriasis patients with different body mass index: a post hoc analysis based on a phase III trial - Wang, Xin; Li, Linfeng (Frontiers in Pharmacology, 2026)
ObjectiveVunakizumab is effective and safe for treating moderate-to-severe plaque psoriasis patients. This post hoc analysis was intended to assess the effects of vunakizumab in patients with different body mass index (BMI).MethodsIn the phase III trial of vunakizumab (NCT04839016), 461 moderate-to-severe plaque psoriasis patients receiving vunakizumab were enrolled and categorized into baseline BMI<24 kg/m2 (N = 179), 24≤BMI<28 kg/m2 (N = 183), and BMI≥28 kg/m2 (N = 99) groups. At least 75% improvement from baseline in the Psoriasis Area and Severity Index (PASI 75), PASI 90, PASI 100, static physician’s global assessment (sPGA) 0/1, patient-reported outcomes (PROs), serum concentration of vunakizumab, and adverse events from week 0 (W0)-W52 were recorded.ResultsA lower BMI was associated with higher W0--W12 accumulating PASI 75, PASI 90, PASI 100, and sPGA 0/1 response rates. From W0--W52, a lower BMI was associated with higher PASI 75, PASI 90, and PASI 100 scores at most time points and was related to sPGA 0/1 response rates from W4--W48. With respect to PROs, higher BMI was related to increased mean dermatology life quality index scores at several time points but was not associated with the mean worst itch numerical rating scale, EuroQoL-5D (EQ-5D) utility index, EQ-5D visual analog scale score, or short form-36 mental/physical component score. A lower BMI was related to a higher mean serum concentration of vunakizumab. The incidences of any adverse events and most specific adverse events did not differ among the groups.ConclusionA lower BMI is associated with a greater treatment response and quality of life in moderate-to-severe plaque psoriasis patients receiving vunakizumab.